2021
DOI: 10.3390/cancers13225673
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Centromere-Associated Kinesin (MCAK/KIF2C) Regulates Cell Migration and Invasion by Modulating Microtubule Dynamics and Focal Adhesion Turnover

Abstract: The microtubule (MT) cytoskeleton is crucial for cell motility and migration by regulating multiple cellular activities such as transport and endocytosis of key components of focal adhesions (FA). The kinesin-13 family is important in the regulation of MT dynamics and the best characterized member of this family is the mitotic centromere-associated kinesin (MCAK/KIF2C). Interestingly, its overexpression has been reported to be related to increased metastasis in various tumor entities. Moreover, MCAK is involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…According to An et al (20), KIF2C increased cancer growth and was linked to tumor immune cell infiltration in endometrial cancer. According to Ha et al (21), KIF2C promotes tumor cell motility and invasion. Furthermore, Zhu et al suggested that KIF2C is a new player in the DNA damage response (22).…”
Section: Introductionmentioning
confidence: 99%
“…According to An et al (20), KIF2C increased cancer growth and was linked to tumor immune cell infiltration in endometrial cancer. According to Ha et al (21), KIF2C promotes tumor cell motility and invasion. Furthermore, Zhu et al suggested that KIF2C is a new player in the DNA damage response (22).…”
Section: Introductionmentioning
confidence: 99%
“…Although at first glance this may appear paradoxical in light of the tightly regulated DCLK1/MT interactions, it could suggest that affecting the ratio of DCLK1 bound to MTs interferes with proper MT dynamics, which underpins mitosis, cell signaling, trafficking migration and other cancer-relevant activities. Indeed, such a bimodal mechanism on MT dynamics has been demonstrated for MT depolymerase mitotic centromere-associated kinesin (MCAK) [ 123 ]. However, there may be DCLK1-dependent tumor-promoting mechanisms independent of its MT association.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of KIF2C could promote cancer cell proliferation, migration, invasion, and metastasis by increasing the mTORC1 signaling transduction [ 21 ]. Moon et al reported that KIF2C was able to control cancer cell migration and invasion through modulating MT dynamics and focal adhesion turnover [ 27 ]. Several previous studies have shown that KIF2C and other kinesins were overexpressed in breast cancer and associated with worse prognosis [ 29 33 ].…”
Section: Introductionmentioning
confidence: 99%